Waste Management Education Enhances Healthy Living Behavior - Wahyu Ramadhani, Reza; Camara Indriani, Dilla; Auliya, Jumi; Rahma Adila, Alfina; Fitriana, Risma; Hafizatun Nisa, Elma; Muftadiin, Fatimatul; Asma, Nur; Afiah, Nurul; Anggraeni G, Ike (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Bukit Raya Village, located near Indonesia's new capital city (IKN), faces public health challenges due to rapid population growth and environmental changes. Inappropriate waste management practices, such as waste burning, have led to health problems like acute respiratory infections (ARI) and diarrhea. This necessitates community empowerment to improve waste management and promote healthy living behaviors. Objective : This study aimed to improve community knowledge, awareness, and behavior regarding proper waste management in Bukit Raya Village to address public health issues. Research Methods/ Implementation Methods : An intervention program called BERSIH (Together with Waste Regulation Education for Healthy Living) was implemented. This program included the creation of educational videos and the socialization of waste regulations using interactive lecture methods. Results : The evaluation results showed a 46% increase in knowledge regarding waste disposal regulations after the outreach program. Additionally, all respondents (57 people) who voted through the official Instagram account of Bukit Raya Village stated that the educational video was beneficial to them. Conclusion/Lesson Learned : The BERSIH program successfully increased awareness of the importance of environmental quality and public health in Bukit Raya Village. Community engagement through educational videos and interactive lectures can effectively improve knowledge and promote proper waste management practices.